Food Security, Affordable Housing, and Poverty: An Islamic Finance Perspective - Arrazi, Muhammad Fakhrul (Universitas Islam Internasional Indonesia, 2023)
Ahmet Suayb Gundogdu, Food Security, Affordable Housing, and Poverty: An Islamic Finance Perspective. Cham: Palgrave Macmillan, 2023, XX + 190 pp. ISBN 978-3-031-27688-0, Price EUR 109.99. Ahmet Suayb Gundogdu is a practitioner and an academic on the subject of Islamic finance. Since first joining the Islamic Development Bank (IDB) in 2008, he has worked his way up to the position of senior professional at the bank. He obtained his doctorate in Islamic finance from Durham University (UK), and besides being a finance practitioner, he also holds the esteemed position of associate professor at Istanbul Sabahattin Zaim University in Turkey. His professional background places him in an ideal position to discuss Islamic finance.